TEKNOLOGI PABRIK DAN PERUMUSAN STRATEGI SEBAGAI UPAYA MEMPERTINGGI DAYA KOMPETISI DAN MENINGKATKAN KINERJA PERUSAHAAN MANUFAKTUR - Yolanda Masnita Siagian (Universitas Trisakti, 2001)
To be successful in this globally and rapidly changing environment, organizations must formutate strategic plans that are consistentwith theirinvestment in and use of manufacturing technology. This studypropose that organizations that invest in advanced manufacturing technology and develop mechanisms for manufacturing managers to participate in strategy fomulation will have improved competitive capabilities and better performance than fims that do not. Using 14 manufacture's sample, this study develops validand reliable measures of advancedmanufacturing technology and manufacturing manager's participation in strategy formulation as well as competitive advantage of a firm. Rank Speraman's results show that the relationships between a fim's practices in these are found to be statistically significant and positive. Also, high levels of these competitive capabilities lead to high levels of performance as measured by customer satisfaction and marketing performance. areas and its competitive capabilities